Religiosity and happiness of Turkish speaking Muslims: does country happiness make a difference?. Issue 7 (9th August 2021) - Esat, Gulden; Day, Susan; Smith, Bradley H.
ABSTRACT: Contextual factors influence the relationship between religiosity and happiness, with sex and country of residence identified as salient moderators. This study used questionnaire data from Turkish speaking Muslims residing in different parts of the world, including 50% in the United States, 20% in Europe, and 15% in Turkey. The study investigated the relationship between religiosity and happiness in the context of the residence country. The happiness score of the country (from the World Happiness Report), the individual's sex, and personal religiosity levels, measured by the Duke University Religion Index were expected to interact to explain the variation in individual happiness. A main effect of country happiness on individual happiness was found, with no moderation effects. Sex moderated the relationship between religiosity and individual happiness, with no correlation for women and a moderate, positive correlation for men. Turkish speaking Muslim women were happier than men in Turkey, while happy at the same level with men in other countries.